Nano-structured gratings for improved light absorption efficiency in solar cells - Masouleh, F.; Das, Narottam; Rozati, S. (2016)
© 2016 by the authors. Due to the rising power demand and substantial interest in acquiring green energy from sunlight, there has been rapid development in the science and technology of photovoltaics (PV) in the last few decades. Furthermore, the synergy of the fields of metrology and fabrication has paved the way to acquire improved light collecting ability for solar cells. Based on recent studies, the performance of solar cell can improve due to the application of subwavelength nano-structures which results in smaller reflection losses and better light manipulation and/or trapping at subwavelength scale. In this paper, we propose a numerical optimization technique to analyze the reflection losses on an optimized GaAs-based solar cell which is covered with nano-structured features from the same material. Using the finite difference time domain (FDTD) method, we have designed, modelled, and analyzed the performance of three different arrangements of periodic nano-structures with different pitches and heights. The simulated results confirmed that different geometries of nano-structures behave uniquely towards the impinging light.